Early identification of disease progression in ALK-rearranged lung cancer using circulating tumor DNA analysis - Angeles, Arlou Kristina J.; Christopoulos, Petros; Yuan, Zhao; Bauer, Simone; Janke, Florian; Ogrodnik, Simon John; Reck, Martin; Schlesner, Matthias; Meister, Michael; Schneider, Marc; Dietz, Steffen; Stenzinger, Albrecht; et al. (npj precision oncology, 2021)
Targeted kinase inhibitors improve the prognosis of lung cancer patients with ALK alterations (ALK+). However, due to the emergence of acquired resistance and varied clinical trajectories, early detection of disease progression is warranted to guide patient management and therapy decisions. We utilized 343 longitudinal plasma DNA samples from 43 ALK+ NSCLC patients receiving ALK-directed therapies to determine molecular progression based on matched panel-based targeted next-generation sequencing (tNGS), and shallow whole-genome sequencing (sWGS). ALK-related alterations were detected in 22 out of 43 (51%) patients. Among 343 longitudinal plasma samples analyzed, 174 (51%) were ctDNA-positive. ALK variant and fusion kinetics generally reflected the disease course. Evidence for early molecular progression was observed in 19 patients (44%). Detection of ctDNA at therapy baseline indicated shorter times to progression compared to cases without mutations at baseline. In patients who succumbed to the disease, ctDNA levels were highly elevated towards the end of life. Our results demonstrate the potential utility of these NGS assays in the clinical management of ALK+ NSCLC.